Bench Performance Test Research of Gear Oil of 80W-140 Type Unmanned Helicopter Main Gearbox - Hongtao Huang; Wenbo Xu; Shijun Liu; Zhaojun Zhang; Xiaojun Zhang; Jiusheng Li (Jixie chuandong)
In order to realize the localization of unmanned helicopter gear oil，the influence of different performance gear oil on gearbox performance is clarified，so as to improve the reliability and service life of gearbox scientifically. Zhengzhou Research Institute of Mechanical Engineering Co.， Ltd.， jointly developed 80W-140 unmanned helicopter gear oil. Based on the performance test of the oil in the laboratory，the performance of the 80W-140 unmanned gear oil is compared and tested with that of the imported oil through the gearbox comprehensive test bench. The vibration，noise，temperature，efficiency and gluing torque obtained from the bench test are carried out，the results show that different performance oils have obvious different effects on the efficiency and bearing capacity of the gearbox， the 80W-140 oil product has better friction reduction，anti-wear and anti gluing performance，which can effectively improve the reliability of the gearbox.